Comparative evaluation of a bioabsorbable collagen membrane and connective tissue graft in the treatment of localized gingival recession: A clinical study - Harsha Mysore Babu; Sheela Kumar Gujjari; Deepak Prasad; Praveen Kumar Sehgal; Aishwarya Srinivasan (Wolters Kluwer Medknow Publications, 2011)
Background: Gingival recession (GR) can result in root sensitivity, esthetic concern to the patient, and predilection to root caries. The purpose of this randomized clinical study was to evaluate (1) the effect of guided tissue regeneration (GTR) procedure using a bioabsorbable collagen membrane, in comparison to autogenous subepithelial connective tissue graft (SCTG) for root coverage in localized gingival recession defects; and (2) the change in width of keratinized gingiva following these two procedures. Materials and Methods: A total of 10 cases, showing at least two localized Miller's Class I or Class II gingival recession, participated in this study. In a split mouth design, the pairs of defects were randomly assigned for treatment with either SCTG (SCTG Group) or GTR-based collagen membrane (GTRC Group). Both the grafts were covered with coronally advanced flap. Recession depth (RD), recession width (RW), width of keratinized gingiva (KG), probing depth (PD), relative attachment level (RAL), plaque index (PI), and gingival index (GI) were recorded at baseline, 3 and 6 months postoperatively. Results: Six months following root coverage procedures, the mean root coverage was found to be 84.84% ± 16.81% and 84.0% ± 15.19% in SCTG Group and GTRC Group, respectively. The mean keratinized gingival width increase was 1.50 ± 0.70 mm and 2.30 ± 0.67 mm in the SCTG and GTRC group, respectively, which was not statistically significant. Conclusion: It may be concluded that resorbable collagen membrane can be a reliable alternative to autogenous connective tissue graft in the treatment of gingival recession.